Genetic analysis of bovine respiratory syncytial virus in Croatia. (June 2018) - Krešić, Nina; Bedeković, Tomislav; Brnić, Dragan; Šimić, Ivana; Lojkić, Ivana; Turk, Nenad
Highlights: Two new subgroups of bovine respiratory syncytial virus were observed in Croatia. New subgroup VIII strains dominated in 2014–2016, replacing subgroup VII strains. Subgroup II and new subgroup VIII strains co-circulated in Croatia. Subgroups II and VII harbour unique mutations in G gene, allowing immune escape. Intensive bovine vaccination resulted in emergence of new virus variants. Abstract: Bovine respiratory syncytial virus (BRSV) represents an important causative agent of respiratory tract disease in cattle. This study describes the genetic diversity of BRSV strains detected in beef cattle herds in Croatia during four consecutive years, from the end of 2011 to April 2016. Genetic diversity of circulating Croatian strains is reflected in their clustering within three different genetic subgroups. Analysis of representative BRSV G gene sequences revealed that infections in Croatia were caused by BRSV strains belonging to two new subgroups (VII and VIII identified herein for the first time). In 2014–2016, the subgroup VII strains were replaced with BRSV strains clustered in the previously unidentified subgroup VIII. Furthermore, co-circulation of subgroup II and new subgroup VIII strains in Croatia was recorded in the same time period. Sequences of Croatian BRSV strains within subgroups II and VII revealed unique mutations within an essential immunodominant region, demonstrating continuous evolution of viral mechanisms for immune escape.